PENDEKATAN HISTOLOGI INSANG DAN HATI IKAN NILA (Oreochromis niloticus) SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN ALAMI DI INDONESIA: LITERATUR REVIEW - Aulia Devani Putri; Gabriella Jessica Agatha; Sandi Fransisco Pratama (Universitas Cokroaminoto Palopo, 2026)
The quality of freshwater in Indonesia has declined due to increasing anthropogenic pressures, particularly from heavy metals, agricultural waste, and industrial waste. A bioindicator approach based on the biological response of aquatic organisms is needed to complement conventional water quality monitoring. This review article aims to examine changes in the histology of the gills and liver of tilapia (Oreochromis niloticus) as a bioindicator of freshwater quality in Indonesia. The method used was a literature review of scientific articles obtained from Google Scholar, Garuda, and ScienceDirect. Articles were selected based on the suitability of the research location in Indonesia, the use of tilapia as the object, and the histological analysis of the gills and/or liver. The results of the review show that water pollution in Indonesian lakes and rivers, especially by heavy metals and anthropogenic activities, consistently causes histological changes in the gills and liver of tilapia. The dominant lesions in the gills included hyperplasia, edema, lamella fusion, epithelial lifting, and telangiectasis, while in the liver, fatty degeneration, hydropic degeneration, cytoplasmic vacuolation, karyolysis, and karyorrhexis were found. These patterns of change reflect the cause-and-effect relationship between the type and intensity of pollutants and the degree of tissue damage. These findings confirm that the histological approach to tilapia gills and liver has strong potential as a biological bioindicator in monitoring and sustainable management of freshwater quality in Indonesia.